Prevotella Induces the Production of Th17 Cells in the Colon of Mice - Yuan Huang; Jinhua Tang; Zheng Cai; Keqiang Zhou; Liang Chang; Yinlan Bai; Yueyun Ma (Journal of Immunology Research)
Th17-mediated mucosal inflammation is related to increased Prevotella bacterial abundance. The actual involvement of Prevotella in the development and accumulation of intestinal Th17 cells at a steady state, however, remains undefined. Herein, we investigated the role of Prevotella in inducing intestinal Th17 cells in mice. Mice were treated with a combination of broad-spectrum antibiotics (including ampicillin, neomycin sulfate, vancomycin hydrochloride, and metronidazole) in their drinking water for 4 weeks and then gavaged with Prevotella for 4 weeks. After inoculation, 16S rDNA sequencing was used to verify the colonization of Prevotella in the colon of mice. The IL-17A as well as IL-17A-expressing T cells was localized and quantified by an immunofluorescence assay (IFA) of colon sections. Th17 cells in the mesenteric lymph nodes of mice were counted by flow cytometry. Systemic immune response to Prevotella colonization was evaluated based on the serum levels of IL-6, TNF-α, IL-1β, IL-17A, IL-10, IL-4, IFN-γ, and IL-2. Th17-polarizing cytokines (IL-6, TNF-α, IL-1β, and IL-2) induced by Prevotella were evaluated by stimulation of bone marrow-derived dendritic cells (BMDCs). Results revealed that after inoculation, Prevotella successfully colonized the intestine of mice and induced the production and accumulation of colonic Th17 cells in the colon. Moreover, Prevotella elevated some of the Th17-related cytokines in the serum of mice. And Th17-polarizing cytokines (IL-6 and IL-1β) produced by BMDCs were mediated mainly through the interaction between Prevotella and Toll-like receptor 2 (TLR2). In conclusion, our data suggest that Prevotella induces the production of Th17 cells in the colon of mice, thus highlighting the potential role of Prevotella in training the intestinal immune system.